2019
DOI: 10.1002/adhm.201801546
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Development of DNA Nanostructures for Potential Healthcare‐Related Applications

Abstract: DNA self‐assembly has proven to be a highly versatile tool for engineering complex and dynamic biocompatible nanostructures from the bottom up with a wide range of potential bioapplications currently being pursued. Primary among these is healthcare, with the goal of developing diagnostic, imaging, and drug delivery devices along with combinatorial theranostic devices. The path to understanding a role for DNA nanotechnology in biomedical sciences is being approached carefully and systematically, starting from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 288 publications
1
64
0
3
Order By: Relevance
“…[109] Nevertheless,the direct comparison of these results is rather challenging,a sthe amount and size of DN vary from study to study. [110] 4. Strategies and Solutions…”
Section: Adverse Immune Responsementioning
confidence: 99%
“…[109] Nevertheless,the direct comparison of these results is rather challenging,a sthe amount and size of DN vary from study to study. [110] 4. Strategies and Solutions…”
Section: Adverse Immune Responsementioning
confidence: 99%
“…DNA nanotechnology can be perceived as being constituted by two major areas: structural DNA and dynamic DNA [9,97]. More focused reviews on DNA nanotechnology have been reported extensively elsewhere [94,96,98]. In the following, we briefly describe several representative DNA architectures and their primary functional characteristics.…”
Section: Overview Dna Nanotechnologymentioning
confidence: 99%
“…Recently, the field has moved from proof-of-concept demonstrations of structural design to more application-oriented research. Custom-built DNA nanostructures are now used in applications such as biosensing, molecular computation, biomolecular analysis, enzyme cascades, material organization and drug delivery (Kizer, Linhardt, Chandrasekaran, & Wang, 2019;Mathur & Medintz, 2019;Wang et al, 2018;Xiao et al, 2019). While the functionality and biocompatibility of DNA makes DNA nanostructures useful in such applications, biostability is still a major challenge in the field.…”
Section: Introductionmentioning
confidence: 99%